P04.23 Multinodular and vacuolating neuronal tumor - advanced MRI features. (9th September 2021) - Ivan, R; Mitrică, M; Sîrbu, O M; Sîrbu, C A
Abstract: BACKGROUND: A rare pathology, multinodular and vacuolating neuronal tumors (MVNT) have been first described in 2013 and included in the 2016 World Health Organization Classification of Tumors of the Central Nervous System as having a distinctive radiological and cytoarchitectural appearance. This study aims to evaluate the imaging features of MVNT, it's differential diagnosis, and possible involvement in adult-onset epilepsy. MATERIAL AND METHODS: We present the case of a 29-year-old male, smoker, and drug abuser, who developed a seizure after 25 hours' sleep deprivation, alcohol, energy drinks, cigarettes, and cocaine consumption. Cerebral CT, MRI, electroencephalogram, MR spectroscopy, and tractography was performed. RESULTS: The MRI performed revealed a right, cortico-subcortical pseudo-nodular temporal lesion, non-enhancing, with a slight thickening of the adjacent cortex and right hippocampal involvement. The neurological examination was normal, but the electroencephalogram showed a right temporal irritative pattern. MR- Spectroscopy described a slight increase of choline (Cho), reduction of N-acetylaspartate (NAA), and also increased myo-inositol peak, ruling out a high-grade tumoral substrate. A tractography was also performed, excluding the other alternative diagnosis of focal cortical dysplasia, thus leaving MVNT to be the most probable explanation for the lesion. CONCLUSION: Advanced MRI features were useful to increase the diagnosis accuracy. The future management consisted of image surveillance, anticonvulsant treatment, and lifestyle improvement. Adult-onset seizures are among the most frequent discovery possibilities for MVNT. In our case, it is to be seen whether the lifestyle changes and medication will prevent future seizures.